Clinical characteristics and risk factors of severe hyponatremia in cirrhotic patients treated with terlipressin. - Pan, Xiaofeng; Zhou, Ziye; Jin, Xiangxiang; Shi, Dawei (Journal of Clinical Pharmacy & Therapeutics, 2020)
What is known and objective: As terlipressin becomes more widely used in clinical practice, more papers had reported the correlation between hyponatremia and terlipressin treatment. This study was performed to evaluate the clinical characteristics and risk factors of severe hyponatremia in cirrhotic patients treated with terlipressin and the effects of concomitant drugs. Methods: We conducted a retrospective evaluation of patients with cirrhosis treated with terlipressin at the gastroenterology department of Hospital between 1 January 2016 and 30 June 2018. Patients treated with terlipressin for gastrointestinal bleeding due to peptic ulcer and other non‐hepatic factors were excluded. Results and discussion: After the patients received terlipressin, their serum sodium concentrations decreased from 138.2 ± 4.3 mmol/L to 129.3 ± 7.2 mmol/L. Statistically significant differences were observed with respect to sex, initial serum sodium concentration, lowest serum sodium concentration, hyponatremia duration and total drug dose. Among the patients with hyponatremia, statistically significant differences in albumin level, serum creatinine level, hyponatremia duration and total drug dose were found between the patients with severe hyponatremia and those with non‐severe hyponatremia. Logistic regression analysis revealed that initial serum sodium concentration (odds ratio, 95% confidence interval: 18.475, 3.967–86.035; P =.000) was a risk factor for reduced serum concentration, and that albumin level (1.105, 1.012–1.207; P =.026), serum creatinine level (0.975, 0.952–0.997; P =.028) and hyponatremia duration (1.297, 1.064–1.583; P =.010) were risk factors of severe hyponatremia. What is new and conclusion: The incidence of severe hyponatremia among patients with cirrhosis who are treated with terlipressin is high. Moreover, higher initial serum sodium concentrations and increased duration of terlipressin administration are associated with a higher the incidence of severe hyponatremia. The initial albumin level is a risk factor for severe hyponatremia as is serum creatinine, although the latter is negatively correlated with the occurrence of the condition.